A GIS-based analysis of the likelihood of adoption of some multi-purpose tree species in East Africa - Conchedda, Giulia; Berhe, Kahsay; Jabbar, M.A. (Informa UK Limited, 2001)
The Multi-purpose Tree (MPT) species have the ability to fit into the farming systems of the East African region where low agricultural productivity, widespread land degradation and hence a diminishing capacity to support the growing human and livestock population are major problems. GIS has been used to develop a spatial representation of the recommendation domains of five MPT species (Calliandra calothyrsus, Sesbania sesban. Leucaena diversifolia. L. pallida and Chamaecytisus palmensis) in Ethiopia. Kenya and Uganda. The recommendation domains were selected based on climatic, edaphic and topographic factors. The likelihood of adoption, within the agro-ecologically suitable areas for each species. has been defined by weighing and combining three factors: the type of land cover/land use: the human and cattle population densities.